Development of the National Etiquette Culture of Future Teachers Based on A Synergistic Approach - Marjan Smatillayevna Janbayeva (Academia One Publishing, 2023)
This article discusses the development of the national etiquette culture of future teachers based on a synergistic approach
Keywords: synergetics; etiquette; innovation